Síntomas obsesivo-compulsivos en adultos policonsumidores de sustancias psicoactivas de un sector de la ciudad de Ibagué (2016)
The aim of this study is to assess the severity of obsessive-compulsive psychoactive in adults who polydrug use in a sector of the city of Ibague (Tolima) by applying the Yale-Brown (1986) scale trends substances. This cross-sectional, empirical research is a quantitative analytical study based on articles and theories about the socio-ecological model of Bronfenbrenner (1979). The study found that 56.6% of the population is at a moderate level of obsessions and compulsions (50%). Also, the correlation between variables of the subscales of obsessions and compulsions as the Pearson coefficient was positive (r = 0.517; p = 0.003), indicating that the increase of obsessions is analogous to increased compulsions oriented towards polydrug use of psychoactive substances.